Association between vitamin A, retinol intake and blood retinol level and gastric cancer risk: A meta-analysis. Issue 4 (August 2015) - Wu, Yihua; Ye, Yao; Shi, Yu; Li, Peiwei; Xu, Jinming; Chen, Kun; Xu, Enping; Yang, Jun
Summary Background & aims The association between dietary vitamin A, retinol intake and blood retinol level and gastric cancer risk has been investigated by many studies. However, the results of these studies were controversial. The aim of our study was to systematically assess this issue. Methods PUBMED and EMBASE were searched, supplemented with manual-screening for relevant publications. Meta-analyses were performed to evaluate the association between vitamin A, retinol dietary intake or blood retinol level and gastric cancer risk. Results Thirty-one studies were included in this meta-analysis. Comparing the highest with the lowest categories, vitamin A intake significantly reduced gastric cancer risk (pooled RR = 0.66, 95% CI: 0.52–0.84), whereas a marginally inverse association was found between retinol intake (pooled RR = 0.94, 95% CI: 0.87–1.03) or blood retinol level (pooled RR = 0.87, 95% CI: 0.73–1.05) and gastric cancer risk. Interestingly, the results of subgroup analysis indicated that high vitamin A intake and blood retinol level were associated with reduced gastric cancer risk in Western countries, while a marginally inverse association was found between retinol and gastric cancer risk in Western countries. Conclusions Vitamin A intake was inversely associated with gastric cancer risk, while no significant association was found with retinol intake or blood retinol level.